2011
DOI: 10.1016/j.jtcvs.2010.11.064
|View full text |Cite
|
Sign up to set email alerts
|

The easier, the better: Age, creatinine, ejection fraction score for operative mortality risk stratification in a series of 29,659 patients undergoing elective cardiac surgery

Abstract: The age, creatinine, ejection fraction score provides an accuracy level comparable to that of the European System for Cardiac Operative Risk Evaluation, with far superior clinical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 19 publications
1
56
0
1
Order By: Relevance
“…Based on the ‘law of parsimony’ or ‘the Ockham razor’ concept, whereby a simple model can explain a phenomenon with the same level of accuracy as complex models, ACEF was shown to be least comparable to the EuroSCORE (composed of 17 variables)24 25 in predicting in-hospital mortality after CABG 22 23…”
Section: Augmenting the Anatomical Syntax Score With Clinical Factorsmentioning
confidence: 99%
“…Based on the ‘law of parsimony’ or ‘the Ockham razor’ concept, whereby a simple model can explain a phenomenon with the same level of accuracy as complex models, ACEF was shown to be least comparable to the EuroSCORE (composed of 17 variables)24 25 in predicting in-hospital mortality after CABG 22 23…”
Section: Augmenting the Anatomical Syntax Score With Clinical Factorsmentioning
confidence: 99%
“…The ACEF score was previously demonstrated by internal validation to have better global performance than more complex mortality scores, and even a large external validation study demonstrated that the ACEF score has noninferior accuracy and better clinical performance with respect to the additive and logistic euroSCORE. 9 Risk estimation in cardiac surgery is an evolving issue. Several questions have not been yet addressed, and new advances in techniques and perioperative care are moving the attention from the general population toward specific subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the time, Tu et al [40], and, currently, Ranucci et al [41] tested this proposition (PANEL Group) and concluded that simpler models containing only essential variables not only would reduce the risk of juxtaposition, multicollinearity, and human error, but would also be cheaper than complex models. That is the explanation for dropping the number of variables collected per patient for EuroScore and EuroScore II, from 97 to 29, respectively.…”
Section: Discussionmentioning
confidence: 99%